Peningkatan peran kelompok pendukung gizi balita di masyarakat di masa pandemi Covid-19 - Agrina Agrina; Erika Erika; Yesi Hasneli (Unri Conference Series: Community Engagement, 2020)
The underfive of children is a high-risk group of nutritional problems during the Covid-19 pandemic due to lack of nutritious eating intake, increasingly difficult economic conditions, and child health services (Posyandu) activities were closed. The community service objective was to increase the role of nutrition support groups (posyandu lay workers) in an effort to prevent and overcome nutritional problems for children. The community service targets are 4 posyandu lay workers in Sialang Mungu district, Pekanbaru as well as families with nutritional problems. The method used nutrition training for posyandu lay worker, screening the nutritional status, guidance to make the simple food (bento), providing nutrition packages and making aquaponic as an effort to endurance nutrition. The success of this activity is measured through the increase of posyandu lay workers to perform nutritional monitoring, the success of making bento, and the increase of weight of children between 500 to 1000 grams. Training and mentoring for nutrition support groups was able to provide the necessary understanding in detecting toddler nutrition during pandemic and making efforts to improve the nutrition of children. Nutrition support groups have the main role to prevent and solve the problem of nutrition of children in the community in Pekanbaru.